2005
DOI: 10.1007/s10565-005-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, cellular uptake and DNA damage by daunorubicin and its new analogues with modified daunosamine moiety

Abstract: Daunorubicin (DRB) and its two analogues containing a trisubstituted amidino group at the C-3' position of the daunosamine moiety have been compared regarding their cytotoxic activity, cellular uptake, subcellular localization and DNA damaging properties. An analogue containing in the amidino group a morpholine moiety (DRBM) as well as an analogue with a hexamethyleneimine moiety (DRBH), tested against cultured L1210 cells, exhibited lower cytotoxicity then DRB. The decrease of cytotoxic activity was not relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
(19 reference statements)
5
21
0
Order By: Relevance
“…However, after 1 h of incubation, daunorubicin was primarily localized in the nucleus (data not shown). This result is consistent with other studies (3,6) and indicates that daunorubicin penetrated the P-gp barrier on the plasma membrane after treatment with actin inhibitors, resulting in more cellular accumulation.…”
Section: Disrupting Traffic Of P-gp-egfp Increases the Accumulation Osupporting
confidence: 93%
“…However, after 1 h of incubation, daunorubicin was primarily localized in the nucleus (data not shown). This result is consistent with other studies (3,6) and indicates that daunorubicin penetrated the P-gp barrier on the plasma membrane after treatment with actin inhibitors, resulting in more cellular accumulation.…”
Section: Disrupting Traffic Of P-gp-egfp Increases the Accumulation Osupporting
confidence: 93%
“…They have a complex mechanism of action, which includes: intercalation into DNA, inhibition of the synthesis of macromolecules, formation of bonds between the nitrogenous bases of DNA, DNA alkylation, DNA crosslinking, inhibition of topoisomerase I and II -key enzymes in DNA synthesis, and formation of free radicals, which damage DNA and lead to lipid peroxidation [1,8]. Initiation of DNA damage through the inhibition of topoisomerase II, leading to the apoptosis, is believed to be a dominant mechanism of therapeutic action of the anthracyclines [8][9][10] as well as of their cardiotoxicity mediated by topoisomerase-IIβ in cardiomyocytes [11]. Topoisomerases are enzymes, which cause the double helix of DNA to be untangled or unwound, a process which is necessary for DNA replication and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical structures of these selected derivatives are also presented in Figure 1.A. It has been shown that these new derivatives of anthracyclines exhibit lower toxicity and cardiotoxicity, together with an ability to overcome the barrier of drug resistance in vitro, as well as high anticancer activity in comparison to the parent compounds (DNR, DOX, EDNR and EDOX) [10,20,22]. Another interesting analog of anthracycline antibiotics is a derivative of DNR -oxazolinodaunorubicin (DNR-OXZL) [23].…”
Section: Introductionmentioning
confidence: 99%
“…They exerted cytotoxic and antiproliferative activity by inhibition of topoisomerase II and not by covalent binding to DNA [134,135].…”
Section: Exemplary Chemical Transformations Of Daunomycin-type Antibimentioning
confidence: 99%